Effects of Peripheral Gradient of Color Saturation on the Feeling of Being Dazzled. (May 2019) - Hanada, Mitsuhiko
The feeling of being dazzled that is evoked by images consisting of an achromatic uniform center surrounded by regions with a luminance gradient was investigated. The effects of type of color saturation gradient in the peripheral region on the feeling of being dazzled were examined. Stimulus configuration was also varied. For the stimulus configuration of a disk-annulus, the feeling of being dazzled was lower for an increasing saturation gradient from the center to the periphery than for decreasing and no-saturation gradients when the center and the periphery maximum luminances were the same. This suggests that the presence of a chromaticity difference between the disk and the surrounding annulus strengthens the feeling of being dazzled. Similar results were obtained for the stimulus configuration of a star shape. For the stimulus configuration of a cross shape, quite different results were obtained; the chromaticity discontinuity had little or opposite effect. These results suggest that chromaticity border and stimulus configurations are factors in the feeling of being dazzled that is evoked by images with luminance gradient.